"Adopting self-sacrifice": how Iranian women cope with the sexual problems during the menopausal transition? An exploratory qualitative study. (3rd July 2017) - Bahri, Narjes; Latifnejad Roudsari, Robab; Azimi Hashemi, Mozhgan
Abstract: Objective: In the menopausal transition sexual problems are an important issue and one of the most frequently presented health concerns of women attending menopause clinics. This study aimed to explore the ways of managing sexual dysfunctions during the menopausal transition among Iranian women. Methods: This exploratory qualitative study was conducted in Iran, from May 2013 to April 2015. Twenty-one women in three stages of menopausal transition, aged 42–55 years old, were purposively selected from urban health centers in Mashhad and Gonabad, Iran. Semi-structured in depth interviews were conducted for data collection until data saturation was achieved. All interviews were recorded electronically and transcribed verbatim. Conventional content analysis was used for data analysis using Granehiem and Lundman (2004) recommended method. MAXQDA 2007 software was used for organizing data and managing the process of analysis. Results: Data analysis demonstrated one overarching theme entitled "Adopting self-sacrifice" consisting of three categories and seven sub-categories. Major categories included: (1) Confronting decline of libido with two subcategories of women's libido decline and inability to fulfill husbands' sexual needs, (2) Seeking strategies for coping with two subcategories of looking for experiences of peer menopausal women and choosing how to interact with the husband and (3) Achieving problem solving strategies with three sub-categories of obedience in sexual relationships ( Tamkin ), employing affection based on religious advice, and giving up own right to reach mutual understanding. Conclusions: The major finding of this study was "Adopting self-sacrifice" in the process of managing sexual dysfunctions during the menopausal transition. The reason for choosing this passive approach by the majority of women has deep roots in their cultural and traditional beliefs.